DC-DC Converters For Hydrogen Fuel Cell Control: A Comprehensive Literature Review - Mohd Shafie Bakar; Mohd Shawal Jadin; Mohd Herwan Sulaiman; Nugroho Agung Pambudi; Danar Susilo Wijayanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This paper presents a comprehensive literature review of recent advances in DC–DC converter technologies for hydrogen fuel cell power conditioning, with particular emphasis on proton exchange membrane fuel cells (PEMFCs) used in electric vehicle and stationary energy systems. Covering 29 peer-reviewed studies, the review examines progress in converter topologies, control methodologies, and performance optimization. The analysis highlights interleaved boost converters combined with advanced control strategies—such as linear quadratic regulator (LQR) control, fractional-order PID control, and sliding mode control—as the current state-of-the-art, achieving efficiencies above 95% while substantially reducing input current ripple and improving transient response. Emerging research trends include high-gain impedance-network converters enabling wide input voltage ranges, isolated and bidirectional converter architectures that support hybrid energy storage integration, and intelligent optimization-based control approaches incorporating particle swarm optimization (PSO) and model predictive control (MPC). The review further identifies key trade-offs in efficiency, power density, voltage gain capability, and dynamic behavior across converter designs, providing a structured foundation for future development of high-performance fuel cell power conditioning systems.